Spatio-temporal requirements of Aurora kinase A in mouse oocyte meiotic spindle building - Blengini, Cecilia S; Vaskovicova, Michaela; Schier, Jan; Drutovic, David; Schindler, Karen (iScience, 2024)
Meiotic spindles are critical to ensure chromosome segregation during gamete formation. Oocytes lack centrosomes and use alternative microtubule-nucleation mechanisms for spindle building. How these mechanisms are regulated is still unknown. Aurora kinase A (AURKA) is essential for mouse oocyte meiosis because in pro-metaphase I it triggers microtubule organizing-center fragmentation and its expression compensates for the loss of the two other Aurora kinases (AURKB/AURKC). Although knockout mouse models were useful for foundational studies, AURK spatial and temporal functions are not yet resolved. We provide high-resolution analyses of AURKA/AURKC requirements during meiotic spindle-building and identify the subcellular populations that carry out these functions: 1) AURKA is required in early spindle assembly and later for spindle stability, whereas 2) AURKC is required in late pro-metaphase, and 3) Targeted AURKA constructs expressed in triple AURK knockout oocytes reveal that spindle pole-localized AURKA is the most important population controlling spindle building and stability mechanisms.
Keywords: cell biology